O trabalho das assistentes sociais nos hospitais do sudoeste do Paraná no contexto pandêmico da Covid-19 - KieKow, Priscila (2023)
The object of this research is the work of professional social workers who work on the front line of Covid-19 treatment at the hospital unit that is part of the 8th Regional Health Department in the state of Paraná. The institutional context of Brazilian public hospitals was one of the workplaces that most needed to be remodeled with the arrival of Covid-19. The object of this study is the work of the professional social workers who work on the front line of Covid-19 treatment at the hospital unit that is part of the 8th Regional Health Department in the state of Paraná. The institutional context of Brazilian public hospitals was one of the workplaces that most needed to be remodeled with the arrival of Covid-19. In this way, where institutional dynamics and flows needed to be redefined quickly based on the new demand, the Social Work teams at the public hospital in the southwestern region of Paraná found themselves facing an emergency situation, and in this sense we sought to understand how the reorganization of the category occurred. The aim of the research is to analyze the work of social workers on the front line in the fight against Covid-19, and the specific objectives of this study are as follows: a) to highlight the dismantling of the Unified Health System (SUS), starting in 2016, with the Temer government and sequentially with the Bolsonaro government; b) to analyze the condition of social workers as salaried workers; c) to understand the work of social workers in urgent and emergency care units belonging to the 7th and 8th Health Regional Offices in southwest Paraná prior to the pandemic; and d) to highlight the demands placed on social workers in public hospital units in the 7th and 8th Health Regional Offices in southwest Paraná, in the context of the Covid-19 pandemic. This is a study with a qualitative approach through empirical research, using sources and documents provided by the hospitals, with the authorization of the institutions. The subjects of this study will be the professional social workers working in the hospital units of the Regional Health Departments in the southwest of Paraná. The criteria established for participation in the study are: having an active registration with the Regional Council of Social Work - CRESS/PR, having an active employment relationship with the hospital unit being researched and working as a technician. The data was collected through semi-structured interviews with the professionals who make up the technical staff of the Social Work sector in the hospital units. The study covered a universe of 08 (eight) professionals, of which 04 (four) participated. The researcher used content analysis as a method for analyzing the data collected. The results showed two main aspects regarding the work of social workers: the increasing precariousness of contracts and working conditions for social workers, highlighting the importance of understanding their condition as salaried workers and their crucial role in health policy in the face of demands and attributions in the pandemic context.